Using digital tools in STEM education and the impact on student creativity in the field of tribology - Skakov, Мazhyn; Ramankulov, Sherzod; Nurizinova, Мakpal; Kurbanbekov, Bakitzhan; Dossymov, Yelmurad (Institute of Advanced Engineering and Science, 2025)
From a preliminary analysis of the scientific literature, it can be seen that knowledge of science, technology, engineering and mathematics (STEM) has a positive impact on the development of necessary skills in students’ professional activities. However, there are very few studies on the effectiveness of using STEM elements in developing the creativity of future physics teachers in specialized fields. The aim of this study was to develop digital resources as a basis for STEM knowledge and to assess their impact on the development of students’ creativity. Based on special principles of education, constructive method in teaching, modeling methods, digital educational resources were developed and an evaluation experiment was conducted. The experiment involved 86 students (40 in the control group and 46 in the experimental group), and compared the results of traditional learning and STEM learning by using digital resources. The results of the questionnaire assessment showed that STEM education can be very effective in developing students’ creativity. The pedagogical experiment was implemented during the teaching of the author’s course entitled “The physical foundations of tribology.” The results of the study contribute to finding solutions to scientific problems in the field of teaching tribology.